Preparation method of environment-friendly rich mineral paper

By superfine powder treatment of coal gangue, combined with corona treatment and the use of hydrated magnesium silicate, the problem of poor toughness of stone paper is solved, and stone paper with higher toughness is prepared, suitable for environmentally friendly packaging materials.

CN119841579APending Publication Date: 2025-04-18江苏江林易海新材料科技发展有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510083382.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing stone paper has poor toughness and is difficult to replace traditional wood pulp paper in practical applications.

Method used

Stone paper with higher toughness was prepared by crushing and grinding coal gangue into ultrafine powder, combined with corona treatment, hydrated magnesium silicate and polymer.

Benefits of technology

It significantly improves the toughness of stone paper, reduces the risk of embrittlement, makes it more suitable for use as an environmentally friendly packaging material, and avoids the consumption of water and harmful gases during traditional papermaking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841579A_ABST
    Figure CN119841579A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new material preparation, and discloses a preparation method of environment-friendly rich mineral paper. According to the present invention, the specially-manufactured ultrafine coal gangue powder is adopted, such that the uniform particle size and the fineness are ensured, the stress concentration point caused by the large particle is reduced, the embrittlement risk is reduced, and the ultrafine coal gangue powder has the large surface area and the large pore structure so as to easily produce the rich mineral paper. In the preparation process, a gradual cooling mode is adopted, so that the paper is gradually shaped in different stages, internal stress concentration points caused by rapid cooling are reduced, and the tear resistance is further improved. In addition, bleaching is not needed in the production process, and the risks of heavy metal residues, fluorescent agents and the like are avoided. The rich mineral paper prepared by the method disclosed by the invention is damp-proof and waterproof, and is particularly suitable for a humid environment. The surface is smooth and flat, and ink blooming is avoided during writing. And automatic weathering can be realized in a field exposed environment. And if being incinerated, the material is easy to incinerate and does not generate black smoke.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material manufacturing technology, and specifically relates to a method for preparing environmentally friendly stone paper. Background Art

[0002] In modern society, with the rapid development of industrialization and urbanization, environmental protection has become one of the core issues of global concern. As an important basic industry, the traditional papermaking industry, while providing paper products, also faces serious environmental problems. The traditional papermaking process relies on wood fiber, which not only consumes a large amount of forest resources, but also produces pollutants such as wastewater and exhaust gas during the production process, which has a negative impact on the ecological environment. In addition, due to the long growth cycle of trees, excessive logging may lead to land degradation, soil erosion and other problems, which in turn affects the ecological balance.

[0003] In recent years, people have begun to pay attention to the concept of circular economy, that is, to reduce waste emissions by improving resource utilization and achieve coordination between economic development and environmental protection. In this context, finding alternative traditional papermaking materials has become a research hotspot. Stone paper, as a new type of environmentally friendly material, has good physical properties and printing adaptability because its main component is calcium carbonate (CaCO3), and it requires almost no water in the production process and does not release harmful gases. Therefore, it is regarded as an ideal green packaging material.

[0004] The concept of stone paper first appeared in the late 1970s, when some developed countries began to try to use non-wood fiber materials to make paper for environmental protection reasons. After decades of research and development, stone paper has gradually formed a relatively mature production process and technical system. There are two main types of stone paper commonly seen on the market: one is made of natural minerals as the main raw material, such as limestone, marble, etc.; the other is made of synthetic materials with an appropriate amount of inorganic fillers added. Regardless of the type of stone paper, its common feature is that it does not contain plant fibers, but relies on the interaction between high molecular polymers and inorganic fillers to form a stable structure, thereby giving the paper excellent mechanical properties and surface characteristics.

[0005] Although stone paper has many advantages, there are still some problems to be solved in the actual promotion and application process. The existing stone paper preparation methods mostly use chemical leaching to extract calcium components. Although the effect is good, the operation is complicated and energy-intensive, which is not conducive to large-scale industrial production. In addition, stone paper has another disadvantage, that is, compared with wood pulp paper, it has a serious brittleness problem (i.e., poor toughness). If coal gangue can be effectively used in the preparation of stone paper, it can not only solve the environmental problems caused by coal gangue storage, but also provide new raw material options for the papermaking industry and promote the recycling of resources. Summary of the invention

[0006] Purpose of the invention: In view of the shortcomings of the existing technology, the present invention proposes a new method for preparing stone paper using coal gangue as raw material, aiming to overcome the defects of the existing technology and solve the problem of poor toughness of the existing stone paper. It will promote the development of the stone paper industry in a more environmentally friendly and practical direction.

[0007] Technical solution: Coal gangue itself is not an ideal raw material for papermaking, but after specific treatment, it can be used in the manufacture of paper. The present invention crushes the coal gangue raw material, grinds it into powder with a particle size D50 less than 2μm, and then performs corona treatment on the powder to obtain ultrafine coal gangue powder.

[0008] 70-80 parts of the above-mentioned ultrafine coal gangue powder are mixed with 8-10 parts of polyε-caprolactone, 4-6 parts of tributyl acetyl citrate, 0.5-1.5 parts of hydrated magnesium silicate, and less than 2 parts of additives. After mixing evenly, deionized water is added, and the components are dispersed at high speed to uniformly mix, forming a slurry; then granulated by a disc granulator to obtain coal gangue masterbatches; the coal gangue masterbatches are sent to a twin-screw extruder, melted and extruded under heating conditions to become a continuous thin film strip; the film strips immediately enter the bidirectional stretching device after leaving the extruder, with a transverse stretching ratio of 3 to 5 times and a longitudinal stretching ratio of 3 to 5 times. After treatment, the wet paper sheets after molding need to be immediately sent to the drying box, and then natural cooling is taken out to obtain the finished stone paper.

[0009] Specifically, the ultrafine coal gangue powder described in the present invention is obtained by the following method: the large gangue is initially crushed to meet the requirements of subsequent processing equipment. The crushed coal gangue is rapidly heated to 800±20℃. This process needs to be completed in a short time. Through rapid heating, temperature differences can be generated inside and outside the mineral particles, resulting in lattice distortion and stress differences, and forming microcracks, especially for mineral components such as quartz contained, which helps reduce their binding energy and promote subsequent crushing. For the present invention, the temperature increase rate is greater than 200°C / min, preferably 250°C / min. The heated coal gangue was immediately poured into the isopropanol aqueous solution for quenching. Due to the huge temperature difference, the mineral particles exploded instantly. The burst coal gangue is obtained, and it is divided into two parts of equal mass, one part is reserved, and the other part is acid-dissolved, and then the precipitate is obtained by neutralizing alkali. The precipitate is mixed with the above-mentioned spare coal gangue and loaded into a ball mill for grinding. The gangue part treated with acid decomposition (acid leaching) will dissolve some unstable mineral phases and release soluble metal ions. These ions form hydroxide precipitation after NaOH is added. This chemical treatment can change the composition of gangue, exposing more active sites, thereby increasing the reactivity in subsequent treatment or application. At the same time, mixing gangue in two different treatment states will help produce a more uniform and finer particle distribution during the ball milling process, as the hardness and brittleness of the two may differ. Moreover, the treated portions treated with acidolysis and alkali neutralization may introduce new crystalline or amorphous phases. When mixed with the original coal gangue, the formation of new phases can be promoted during the grinding process and further optimize the microstructure of the powder.

[0010] After grinding, the ground slurry is subjected to solid-liquid separation for 10 to 20 minutes. After separation, the solid precipitate is dried and then ground and dispersed to obtain a powder with a particle size D50 less than 2 μm. The powder is evenly spread on the rotating disk of the corona treatment machine, the rotation speed is set to 5-15 rpm, the corona discharge voltage is set to 20 kV, and the current density is about 0.1 mA / cm 2 , the nitrogen flow rate is 1L / min, and the corona discharge device is turned on. During this process, high-energy electrons will impact the surface of the coal gangue particles, causing the surface molecular bonds to break, forming free radicals and other active sites, and changing the surface properties of the powder. The treatment time is 3-5 minutes. After the treatment is completed, the coal gangue powder is obtained.

[0011] In the present invention, hydrated magnesium silicate is creatively added. Specifically, the hydrated magnesium silicate can be cotton-like hydrated magnesium silicate or thin-flaked hydrated magnesium silicate. However, in the present invention, cotton-like hydrated magnesium silicate is preferred. Compared with thin-flaked hydrated magnesium silicate, cotton-like hydrated magnesium silicate can better strengthen the polymer matrix, because cotton-like particles can play the role of skeleton support like fibers, preventing crack propagation, and therefore are particularly effective in improving the tear resistance and flexibility of the finished product. Cotton-like hydrated magnesium silicate has a large specific surface area and an irregular fibrous structure, which can form more contact points and a more complex network structure in the polymer matrix. This structure helps to disperse stress, and when the material is subjected to external force, the load can be distributed more evenly, thereby improving the toughness of the stone paper. In addition, the interfacial interaction between cotton-like hydrated magnesium silicate and polymers such as poly-ε-caprolactone may be more effective. These interactions can be physical entanglement, hydrogen bonds or other weak chemical bonds, which enhance the bonding force between the filler and the matrix, further improving the mechanical strength and toughness of the composite material.

[0012] Specifically, the additives include one or more of surfactants, lubricants, leveling agents, foaming agents, catalysts, and stabilizers. The additives described in the present invention are commonly used additives in the art, and there are no special requirements. They are selected and added in appropriate amounts according to needs.

[0013] Specifically, the specific process parameters of the granulation are: the main engine speed is controlled at 100-600 rpm, the feeder speed is 8-30 rpm, the vacuum degree is maintained at 0.02-0.08 MPa, and the head pressure is maintained at 20-30 MPa.

[0014] Specifically, in the extrusion, the extrusion temperature is controlled between 160°C and 200°C.

[0015] For further improvement, a gradual cooling method is used during the preparation process, so that the paper is gradually shaped at different stages, reducing the internal stress concentration points caused by rapid cooling, thereby improving tear resistance. The specific process is: reduce to 150°C within 2 hours, reduce to 100°C within 2 hours, reduce to 50°C after 2 hours, and finally reduce to room temperature. Or: reduce to 150°C within 2 hours, keep warm for 1 hour, reduce to 100°C within 2 hours, keep warm for 1 hour, reduce to 50°C after 2 hours, keep warm for 1 hour, and finally reduce to room temperature.

[0016] Specifically, the drying is carried out by continuously heating at 60-80° C. for about 2 hours until the moisture content drops below 5%.

[0017] Beneficial effects: Compared with the traditional stone paper preparation method, the present invention selects a wider range of coal gangue as the starting raw material, which not only solves the storage problem of coal gangue waste, but also provides a new source of raw materials for the papermaking industry.

[0018] The preparation method of environmentally friendly stone paper of the present invention adopts specially manufactured ultrafine coal gangue powder to ensure uniform and fine particle size, reduce stress concentration points caused by large particles, reduce the risk of embrittlement, and the ultrafine coal gangue powder has a larger surface area and pore structure, which is conducive to the manufacture of stone paper. Through the comprehensive application of multiple means, the embrittlement problem of existing stone paper (i.e., poor toughness) is solved. In addition, the present invention does not require bleaching, heavy metal residues, fluorescent agents, etc. during the production process.

[0019] The stone paper prepared by the method of the present invention is moisture-proof and waterproof, and is particularly suitable for use in humid environments. The mechanical properties are stronger than those of ordinary wood pulp paper, and the whiteness is better than that of unbleached wood pulp paper and close to that of bleached wood pulp paper. The surface is smooth and flat, and the ink does not smudge when writing. It can automatically weather in an outdoor exposed environment. If burned, it is also easy to burn without producing black smoke. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a cut sample of the stone paper obtained in Example 1. DETAILED DESCRIPTION

[0021] The technical solution of the present application is described in detail below through examples, but the protection scope of the present application is not limited to the examples. The parts described in the present invention are all calculated by mass.

[0022] The additives described in this embodiment can be selected from commonly used additives in the art without special requirements. The additives include but are not limited to one or more of surfactants, lubricants, leveling agents, foaming agents, catalysts, and stabilizers.

[0023] Example 1

[0024] Prepare isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby. Preliminary crushing of bulky coal gangue, rapid heating of crushed coal gangue to about 800°C, heating rate of 250°C / min, pouring heated coal gangue into the above solution immediately for quenching, obtaining coal gangue after explosion, dividing it into two parts of equal mass, one for standby, and adding 6M HCl solution to the other according to the ratio of solid-liquid ratio of 1:10, stirring for 30 minutes at 80°C, after completing the reaction, filtering, slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10, obtaining precipitate, mixing this precipitate with the above-mentioned standby equal mass coal gangue, loading into ball mill together, grinding at a speed of 1500rpm for 60-90 minutes with zirconium oxide ceramic balls (diameter 2mm) as grinding media. After grinding, use a centrifuge to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions, and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm. The above powder is evenly spread on the rotating disk of the corona treatment machine, the rotation speed is set to 10rpm, the corona discharge voltage is set to 20kV, and the current density is about 0.1mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment, ultrafine coal gangue powder is obtained.

[0025] Mix 75 parts of the above-mentioned ultrafine gangue powder with 9 parts of poly-ε-caprolactone, 5 parts of acetyl tributyl citrate, 1 part of cotton-like hydrated magnesium silicate and additives. Mix evenly and put into a slurry mixing barrel, add an appropriate amount of deionized water, start a high-speed disperser to evenly mix the ingredients to form a slurry with a certain viscosity and fluidity.

[0026] Then a disc granulator is used for granulation, the main engine speed is controlled at 100-600 rpm, the feeder speed is 8-30 rpm, the vacuum degree is maintained at 0.02-0.08 MPa, and the head pressure is maintained at 20-30 MPa to obtain coal gangue masterbatch, which is sent to a twin-screw extruder, melted and extruded into continuous film strips under heating conditions, and the extrusion temperature is controlled between 160°C and 200°C.

[0027] After leaving the extruder, the film strips immediately enter the biaxial stretching device, with a transverse stretching ratio of 3 to 5 times and a longitudinal stretching ratio of 3 to 5 times. After treatment, they are cooled and shaped. The formed wet paper sheets need to be immediately sent to the drying oven and heated at 60-80℃ for about 2 hours until the moisture content drops below 5%. After that, they are taken out and cooled naturally to obtain the finished stone paper.

[0028] The cut stone paper samples were tested as follows: Figure 1The results of the photodegradation test using a xenon lamp for 120 hours are as follows: the weight average relative molecular weight decrease rate is 93%; the weight average relative molecular weight after photolysis is <10 4 The molecular percentage is 35%. The stone paper samples were weathered in about 6 months outdoors. It can be seen that this product can be degraded well.

[0029] The samples were tested for printing using common ink types, and the results showed that the stone paper had good ink absorption and clarity, and was suitable for a variety of printing methods.

[0030] Example 2

[0031] Prepare isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby. Preliminary crushing of bulky coal gangue, rapid heating of crushed coal gangue to about 800°C, heating rate of 250°C / min, pouring heated coal gangue into the above solution immediately for quenching, obtaining coal gangue after explosion, dividing it into two parts of equal mass, one for standby, and adding 6M HCl solution to the other according to the ratio of solid-liquid ratio of 1:10, stirring for 30 minutes at 80°C, after completing the reaction, filtering, slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10, obtaining precipitate, mixing this precipitate with the above-mentioned standby equal mass coal gangue, loading into ball mill together, grinding at a speed of 1500rpm for 60-90 minutes with zirconium oxide ceramic balls (diameter 2mm) as grinding media. After grinding, use a centrifuge to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions, and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm. The above powder is evenly spread on the rotating disk of the corona treatment machine, the rotation speed is set to 10rpm, the corona discharge voltage is set to 20kV, and the current density is about 0.1mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment, ultrafine coal gangue powder is obtained.

[0032] Mix 75 parts of the above-mentioned ultrafine gangue powder with 9 parts of poly-ε-caprolactone, 5 parts of acetyl tributyl citrate, 1 part of flaky hydrated magnesium silicate and additives. Mix evenly and put into a slurry mixing barrel, add an appropriate amount of deionized water, start a high-speed disperser to evenly mix the ingredients to form a slurry with a certain viscosity and fluidity.

[0033] Then a disc granulator is used for granulation, the main engine speed is controlled at 100-600 rpm, the feeder speed is 8-30 rpm, the vacuum degree is maintained at 0.02-0.08 MPa, and the head pressure is maintained at 20-30 MPa to obtain coal gangue masterbatch, which is sent to a twin-screw extruder, melted and extruded into continuous film strips under heating conditions, and the extrusion temperature is controlled between 160°C and 200°C.

[0034] After leaving the extruder, the film strips immediately enter the biaxial stretching device, with a transverse stretching ratio of 3 to 5 times and a longitudinal stretching ratio of 3 to 5 times. After treatment, they are cooled and shaped. The formed wet paper sheets need to be immediately sent to the drying oven and heated at 60-80℃ for about 2 hours until the moisture content drops below 5%. After that, they are taken out and cooled naturally to obtain the finished stone paper.

[0035] Example 3

[0036] The basic steps of Example 3 are roughly the same as those of Example 1, except that the cooling and shaping after the stretching treatment adopts a gradual cooling method to control the cooling speed. The specific process is: reduce to 150°C within 2 hours, reduce to 100°C within another 2 hours, reduce to 50°C after another 2 hours, and finally reduce to room temperature.

[0037] Example 4

[0038] The basic steps of Example 4 are roughly the same as those of Example 1, except that the cooling and shaping after the stretching treatment adopts a gradual cooling method to control the cooling speed. The specific process is: reduce to 150°C within 2 hours, keep warm for 1 hour, reduce to 100°C within 2 hours, keep warm for 1 hour, reduce to 50°C after 2 hours, keep warm for 1 hour, and finally reduce to room temperature.

[0039] Comparative Example 1

[0040] Prepare isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby. Preliminary crushing of bulky coal gangue, rapid heating of crushed coal gangue to about 800°C, heating rate of 250°C / min, pouring heated coal gangue into the above solution immediately for quenching, obtaining coal gangue after explosion, dividing it into two parts of equal mass, one for standby, and adding 6M HCl solution to the other according to the ratio of solid-liquid ratio of 1:10, stirring for 30 minutes at 80°C, after completing the reaction, filtering, slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10, obtaining precipitate, mixing this precipitate with the above-mentioned standby equal mass coal gangue, loading into ball mill together, grinding at a speed of 1500rpm for 60-90 minutes with zirconium oxide ceramic balls (diameter 2mm) as grinding media. After grinding, use a centrifuge to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions, and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm. The above powder is evenly spread on the rotating disk of the corona treatment machine, the rotation speed is set to 10rpm, the corona discharge voltage is set to 20kV, and the current density is about 0.1mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment, ultrafine coal gangue powder is obtained.

[0041] Mix 75 parts of the above-mentioned ultrafine gangue powder with 9 parts of poly-ε-caprolactone, 5 parts of acetyl tributyl citrate and additives. Mix evenly and put into a slurry mixing barrel, add an appropriate amount of deionized water, start a high-speed disperser to evenly mix the ingredients to form a slurry with a certain viscosity and fluidity.

[0042] Then a disc granulator is used for granulation, the main engine speed is controlled at 100-600 rpm, the feeder speed is 8-30 rpm, the vacuum degree is maintained at 0.02-0.08 MPa, and the head pressure is maintained at 20-30 MPa to obtain coal gangue masterbatch, which is sent to a twin-screw extruder, melted and extruded into continuous film strips under heating conditions, and the extrusion temperature is controlled between 160°C and 200°C.

[0043] After leaving the extruder, the film strips immediately enter the biaxial stretching device, with a transverse stretching ratio of 3 to 5 times and a longitudinal stretching ratio of 3 to 5 times. After treatment, they are cooled and shaped. The formed wet paper sheets need to be immediately sent to the drying oven and heated at 60-80℃ for about 2 hours until the moisture content drops below 5%. After that, they are taken out and cooled naturally to obtain the finished stone paper.

[0044] Comparative Example 2

[0045] Mix 75 parts of conventional coal gangue powder with 9 parts of poly-ε-caprolactone, 5 parts of acetyl tributyl citrate, 1 part of flaky hydrated magnesium silicate and additives. Mix evenly and put into a slurry mixing barrel, add an appropriate amount of deionized water, start a high-speed disperser to evenly mix the ingredients to form a slurry with a certain viscosity and fluidity.

[0046] Then a disc granulator is used for granulation, the main engine speed is controlled at 100-600 rpm, the feeder speed is 8-30 rpm, the vacuum degree is maintained at 0.02-0.08 MPa, and the head pressure is maintained at 20-30 MPa to obtain coal gangue masterbatch, which is sent to a twin-screw extruder, melted and extruded into continuous film strips under heating conditions, and the extrusion temperature is controlled between 160°C and 200°C.

[0047] After leaving the extruder, the film strips immediately enter the biaxial stretching device, with a transverse stretching ratio of 3 to 5 times and a longitudinal stretching ratio of 3 to 5 times. After treatment, they are cooled and shaped. The formed wet paper sheets need to be immediately sent to the drying oven and heated at 60-80℃ for about 2 hours until the moisture content drops below 5%. After that, they are taken out and cooled naturally to obtain the finished stone paper.

[0048] Comparative Example 3

[0049] Prepare isopropanol aqueous solution (ratio: 10g isopropanol: 500ml water) for standby. Preliminary crushing of bulky coal gangue, rapid heating of crushed coal gangue to about 800°C, heating rate of 250°C / min, pouring heated coal gangue into the above solution immediately for quenching, obtaining coal gangue after explosion, dividing it into two parts of equal mass, one for standby, and adding 6M HCl solution to the other according to the ratio of solid-liquid ratio of 1:10, stirring for 30 minutes at 80°C, after completing the reaction, filtering, slowly adding 5% NaOH solution to the filtrate until the pH value reaches 9-10, obtaining precipitate, mixing this precipitate with the above-mentioned standby equal mass coal gangue, loading into ball mill together, grinding at a speed of 1500rpm for 60-90 minutes with zirconium oxide ceramic balls (diameter 2mm) as grinding media. After grinding, use a centrifuge to separate the solid and liquid of the ground slurry for about 10 to 20 minutes. The separated liquid can be returned to the production process for recycling. The solid precipitate is dried under low temperature (95°C) vacuum conditions, and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm. The above powder is evenly spread on the rotating disk of the corona treatment machine, the rotation speed is set to 10rpm, the corona discharge voltage is set to 20kV, and the current density is about 0.1mA / cm 2 , the nitrogen flow rate is 1L / min, the corona discharge device is turned on, the treatment time is 3 minutes, and after the treatment, ultrafine coal gangue powder is obtained.

[0050] Mix 75 parts of the above-mentioned ultrafine gangue powder with 9 parts of high-density polyethylene, 5 parts of acetyl tributyl citrate, 1 part of cotton-like hydrated magnesium silicate and additives. Mix evenly and put into a slurry mixing barrel, add an appropriate amount of deionized water, start a high-speed disperser to evenly mix the ingredients to form a slurry with a certain viscosity and fluidity.

[0051] Then a disc granulator is used for granulation, the main engine speed is controlled at 100-600 rpm, the feeder speed is 8-30 rpm, the vacuum degree is maintained at 0.02-0.08 MPa, and the head pressure is maintained at 20-30 MPa to obtain coal gangue masterbatch, which is sent to a twin-screw extruder, melted and extruded into continuous film strips under heating conditions, and the extrusion temperature is controlled between 160°C and 200°C.

[0052] After leaving the extruder, the film strips immediately enter the biaxial stretching device, with a transverse stretching ratio of 3 to 5 times and a longitudinal stretching ratio of 3 to 5 times. After treatment, they are cooled and shaped. The formed wet paper sheets need to be immediately sent to the drying oven and heated at 60-80℃ for about 2 hours until the moisture content drops below 5%. After that, they are taken out and cooled naturally to obtain the finished stone paper.

[0053] The relevant test data of Examples 1 to 4 and Comparative Examples 1 to 3 are shown in the following table:

[0054]

[0055] From the above experimental results, it can be seen that the stone paper obtained by the method of the present invention is better than unbleached wood pulp paper in terms of whiteness and close to bleached wood pulp paper. Example 1 adds cotton-like hydrated magnesium silicate, Example 2 adds flaky hydrated magnesium silicate, and Comparative Example 1 does not add hydrated magnesium silicate. It can be seen that in terms of the toughness of the final product, the effect of cotton-like hydrated magnesium silicate is significantly better than that of flaky hydrated magnesium silicate, and flaky hydrated magnesium silicate does not seem to play a corresponding role. Example 3 and Example 4 improve the cooling method. It can be seen that the products obtained in Example 3 and Example 4 have better effects on tear toughness. The raw material of Comparative Example 2 uses conventional coal gangue powder. Compared with the use of ultrafine coal gangue powder, the embrittlement problem is more serious. Comparative Example 3 uses high-density polyethylene. It can be seen that the product is obviously not as tough as poly-ε-caprolactone.

[0056] The above description is only a preferred embodiment of the present application and is not intended to limit the present application.

Claims

1. A method for preparing stone paper, characterized in that: The method comprises the following steps: crushing the coal gangue raw material, grinding it into powder with a particle size D50 less than 2 μm, and then subjecting the powder to corona treatment to obtain ultrafine coal gangue powder; mixing 70-80 parts of the ultrafine coal gangue powder with 8-10 parts of poly-ε-caprolactone, 4-6 parts of acetyl tributyl citrate, 0.5-1.5 parts of hydrated magnesium silicate and additives, adding deionized water after mixing evenly, and dispersing at high speed to make the components evenly mixed to form a slurry; then using a disc granulator to granulate to obtain coal gangue masterbatch; sending the coal gangue masterbatch into a twin-screw extruder, melting it under heating conditions and extruding it into a continuous film strip; the film strip immediately enters a biaxial stretching device after leaving the extruder, with a transverse stretching ratio of 3-5 times and a longitudinal stretching ratio of 3-5 times, cooling and shaping after treatment, and the formed wet paper sheet needs to be immediately sent to a drying oven, and then taken out and naturally cooled to obtain a finished stone paper.

2. The method for preparing stone paper according to claim 1, characterized in that: The ultrafine coal gangue powder is obtained by the following method: preliminarily crushing large pieces of coal gangue, rapidly heating the crushed coal gangue to 800±20℃, with a heating rate greater than 200℃ / min, immediately pouring the heated coal gangue into an isopropanol aqueous solution for quenching to obtain cracked coal gangue, dividing it into two equal parts, one for standby use, and the other for acid hydrolysis, and then neutralizing it with alkali to obtain a precipitate, mixing the precipitate with the above-mentioned equal-weight standby coal gangue, and loading them into a ball mill for grinding. After grinding, the ground slurry is subjected to solid-liquid separation for 10 to 20 minutes, and after separation, the solid precipitate is dried, and then ground and dispersed to obtain a powder with a particle size D50 less than 2μm; the above powder is subjected to corona treatment, and after the treatment is completed, the coal gangue powder is obtained. .

3. The method for preparing stone paper according to claim 2, characterized in that: The corona treatment is as follows: the powder is evenly spread on the rotating disk of the corona treatment machine, the rotation speed is set to 10 rpm, the corona discharge device is turned on, and the treatment time is 3-5 minutes.

4. The method for preparing stone paper according to claim 1, characterized in that: The hydrated magnesium silicate is preferably cotton-like hydrated magnesium silicate.

5. The method for preparing stone paper according to claim 1, characterized in that: The additives include one or more of surfactants, lubricants, smoothing agents, foaming agents, catalysts, and stabilizers.

6. The method for preparing stone paper according to claim 1, characterized in that: The specific process parameters of the granulation are as follows: the main machine speed is controlled at 100-600 rpm, the feeder speed is 8-30 rpm, the vacuum degree is maintained at 0.02-0.08 MPa, and the die head pressure is maintained at 20-30 MPa.

7. The method for preparing stone paper according to claim 1, characterized in that: In the extrusion, the extrusion temperature is controlled between 160°C and 200°C.

8. The method for preparing stone paper according to claim 1, characterized in that: The cooling and shaping process is performed by dropping the temperature to 150° C. within 2 hours, dropping the temperature to 100° C. within another 2 hours, dropping the temperature to 50° C. after another 2 hours, and finally dropping the temperature to room temperature.

9. The method for preparing stone paper according to claim 1, characterized in that: Reduce the temperature to 150℃ within 2 hours, keep warm for 1 hour, reduce the temperature to 100℃ within 2 hours, keep warm for 1 hour, reduce the temperature to 50℃ after 2 hours, keep warm for 1 hour, and finally reduce the temperature to room temperature.

10. The method for preparing stone paper according to claim 1, characterized in that: The drying step is to continue heating at 60-80° C. for about 2 hours until the moisture content drops below 5%.